The Patterns of Distance Learning Communication in The Covid-19 Pandemic Era - Dedeh Fardiah; Neni Yulianita; Yenni Yuniati; Marina Yuliani; Iwan Seppriadi (Universitas Veteran Bangun Nusantara, 2023)
The policy of temporarily closing educational institutions to hold the spread of COVID-19 in Indonesia impacts the learning process being replaced by a learning system using online media application features. Implementation of the distance learning system (PJJ) has various obstacles, including infrastructure, human resources, and the learning process. This study examines communication patterns in the PJJ process. The method used in this research is descriptive quantitative with a population of 13,539 students of the Bandung Islamic University in 2021; 389 people are sampled using the Slovin formula. The study results show that 1) The obstacles of PJJ include infrastructure, system, and lecture climate problems. 2) The solution that must be done in terms of infrastructure is that the students need to prepare backup providers, while in terms of materials, students need to look for additional references from other sources. 3) dependence on internet access can affect financially, which can be burdensome for educators and students. 4) The combination of offline and online learning is considered efficient. However, face-to-face learning is more desirable 5) From a media perspective, Zoom Meeting is a media that is often used. The Moodle e-learning lecture system is widely used, including Google Meet, Google Classroom, and Google Drive. 6) The material in the PJJ process is considered adequate. 7) Online multiple-choice questions in quiz systems dominate the exam system, google forms, and even essay types or a take-home exam. However, there are still a few offline projects and exams.